Tourism media and its role in promoting tourism hotels Baghdad city as an example - Dr. Mohan Shaalan Abbas (Genius Journals, 2023)
The research dealt with "tourist media and its role in tourism hotel promotion". The research seeks to identify the pros and cons, advantages and characteristics of tourism media in tourism hotel promotion processes, as well as in order to improve the status of tourist hotels through the use of modern and advanced media, which, it does not conflict with the objectives and methodology of the research. The research included four main topics, which are as follows: The first topic, tourism media, contained the introduction and the research methodology. It was limited to the research problem, importance, objectives, hypothesis, temporal and spatial research determinants, as well as the research method. As for the second topic, it included the conceptual context of tourism media, the introduction, the concept of tourism media, media functions, the importance of tourism media, media objectives, tourist media outlets, as well as the relationship between media and hotel promotion, followed by the third section, definition and classification of hotels, as well as the types of hotels and elements that participated in the tourism recovery. The concept of hotel promotion also came, the importance and objectives, and how tourism hotel promotion procedures are carried out, and the most important elements of hotel promotion
Keywords: tourism media; promotion; media